Teori Pengetahuan Edmund Husserl - Hardiansyah Hardiansyah (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Edmund Husserl (1859-1938) was born in Prosznitz town in Moravia. Edmund Husserl studied Phenomenology with Franz Brentano, Husserl's very influenced with phenomenology thought founded by Franz Brentano. The uniqueness of knowledge discovery on phenomenology is get while all theories, opinions and views are already known by every one, so that will be able to capture the pure essence. As a measuring is inter-subjective truth, knowledge truth if to explore the meaning behind the phonemenon neomenon towards meta-theory and meta-science. The step methods used are (1) Phenomenological Reduction, (2) Eidetic Reduction, (3) Transcendental Reduction.